Pengaruh Citra Bank Terhadap Loyalitas Nasabah Pada PT. Bank BRI Syariah Kantor Cabang Madiun - Iin Mazuin Agustina (Universitas PGRI Madiun, 2018)
This study aims to analyze the influence of bank image on customer loyalty at PT. BankBRI Syariah Branch Office Madiun. Bank image has an effect on Customer Loyalty this isevidenced from t value on bank image variable (X) is 5,484 with significant level 0.000.Because 5,484 > 1,650 and 0,000 < 0,05 then H0 is rejected and Ha accepted. It can beconcluded that t hitung > t table is greater than t table of significance level of 0.000 is smallerthan 0.05 then the research hypothesis reject H0 and receive Ha. On the basis of correlationtest obtained rth value is 0.327 while r tabel 0.113. This means that the value of r hitung >r tabel (0.327 > 0.113). In this study obtained Y = 25.123 + 0.303 X constant value of 25.123means that if the image variable bank fixed value or kostanta the amount of customer loyaltyis equal to 25.123. This means that without the influence of bank image variables, customerloyalty still has a value of 25.123.